Influence of styrene-acrylic copolymer latex on the mechanical properties and microstructure of Portland cement/Calcium aluminate cement/Gypsum cementitious mortar. (10th December 2019) - Zhang, Xiao; Li, Guoxin; Song, Zhanping
Highlights: Flexural strength and bond strength of TBS were improved by SA polymer. The microstructure of TBS could be enhanced by the SA polymer film. Revealed the improvement mechanism of SA on the TBS. Abstract: The effects of styrene-acrylic copolymer latex (SA) on a ternary binder system (TBS) mortar based on Portland cement/Calcium aluminate cement/Gypsum were studied by means of mechanical properties, tensile bond strength and water absorption. The results demonstrated that the flexural strength and tensile bond strength of TBS mortar can be improved due to the addition of SA polymer. Besides, SA polymer could improve the flexibility and decrease the water absorption of TBS mortar. The reasons behind the results are that hydration of TBS can be promoted with the presence of SA polymer, and the formation of polymer film make the cement matrix denser. SEM and EDS prove that SA polymer film adhering the hydration products bridges the crystals and fills the pores.